Comparative Study and Utilization of Best Deep Learning Algorithms for the Image Processing (International Journal of Innovative Research in Computer Science & Technology, 2022)
Deep learning has gained immense popularity in scientific computing, and its algorithms are  widely used in complex problem-solving industries. Every  deep learning algorithm use different types of neural  networks to perform indented tasks. Deep learning (DL)  algorithms have emerged from different machine learning  and soft computing methodologies. Since then, a number of deep learning (DL) algorithms have been recently  introduced in the scientific community and applied in  various application fields. Today, the use of DLs has  become indispensable due to their intelligence, effective learning, accuracy and reliability in model creation. However, a comprehensive list of DL algorithms has not  yet been presented in the scientific literature. This article  lists the most popular DL algorithms and their application  areas. Deep learning uses ANN artificial neural networks to  perform convoluted calculations on huge amounts of data.  It is a type of machine learning based on the structure and  function of the human brain. Deep learning algorithms train  machines by learning from examples. Industries such as  healthcare, e-commerce, entertainment and advertising  often use deep learning.
Keywords: Deep learning; machine learning; convolutional neural networks (CNN) recurrent neural networks (RNN); autoencoder (DAE); deep belief networks (DBNs); long short-term memory (LSTM); review; survey; state of the art